Analysis of Essential Oils Extracted from Algerian Medicinal Plants and Their Aphicidal Effect Against the Melon Aphid Aphis Gossypii Glover (Homoptera: Aphididae) - Hakimi, Sakina; Araj, Salah-Eddin; Ateyyat, Mazen A.; Bounechada, Mustapha; Demirtas, Ibrahim; Gul, Fatih (Jordan Journal of Agricultural Sciences, 2024)
Chemical insecticides are decisive in controlling insect pests, but they harm the environment. Reducing the use of chemical insecticides has become the main goal for ensuring healthy produce. However, research focusing on plant-based compounds has recently increased. The present study was carried out to analyze essential oils extracted from Algerian medicinal plants by gas chromatography coupled with mass spectrometry (GC-MS) to determine the insecticidal activity of essential oils from Juniperus phoenicea, Rosmarinus officinalis, Lavandula stoechas, Mentha pulegium and Pinus sylvestris, against Aphis gossypii Glover The main components constituting each essential oil were: α-pinene, β-Pinene 1,8- cineol, Linalool, Linalyl acetate, Fenchone, Pulegone, and Camphor. The toxicity of tested essential oils against Aphis gossypii was different and dependent on the concentration used (1000, 10000, and 100000 ppm), the duration of exposure (24, 48, and 72 h), and the chemical composition of the oil. The highest toxicity was for J. phoenicea, M. pulegium, and L. stoechas which were toxic as Actara® insecticide.